Penerapan Produksi Bersih pada Proses Painting Steel Sebagai Upaya Minimasi Limbah (Studi Kasus Pada Industri Perakiton Sepeda Motor) - Priyambada, Ika Bagus (METANA, 2006)
Abstract   Painting Steel process in some automotive industries uses Spray methode, but this methode produce more liquid waste and solid waste. Waste minimization that can be done by Cleaner Production through implementation of Cotionic Electro Deposition (CED) methode. This methode has a purpose to reduce liquid waste and solid waste to achieve minimum environmental effects. After a comparization beetwen Spray methode and CED methode based on the amount of production, paint consumption, watter consumption, electrical consumption, man power consumption ond waste from the production, the result is CED methode has more economical benefit as much as Rp 556.736. 178,00/month. This analyz  doesn't  snatch investment.   Key words : Cleaner Production, Spray methode, CED methode, saving